DISASTER MITIGATION IN FLATS : EVALUATION AND DESIGN OF A DISASTER PREPAREDNESS - Mudjanarko, Sri Wiwoho; Setiawa, M. Ikhsan (Inscientech: Journal of Industrial, Science and Technology, 2017)
Law Number 24 year 2007 on disaster management, mitigation is defined as a series of efforts to reduce disaster risk, either through physical development as well as awareness raising and capacity building facing the threat of disaster. Design of zoning into account key parameters, namely the earthquake zoning based seismic design category. Earthquake Disaster Mitigation in the flats, before disaster: (1) Categorization of areas based on the characteristics of the earthquake zone (seismic zoning); (2) Research the characteristics of land on which will be built flats (flat), whether included soft soil or hard soil; (3) Making a clear evacuation path on the building of towers and the surrounding area; (4) The construction of towers based on building standards for residential/earthquake resistant buildings, ranging from foundation to finish by referring to the building codes in force, such as size of the building (the building that avoid angular or curve) and the configuration of the building; (5) Quality control of the implementation of the building starts from the initial stage to the final stage; (6) The use of special material for reinforcement (retrofitting material), from local materials that are easy to find while saving the cost. While disaster, following guidelines/procedures for emergency earthquake that have been enacted or have been given training by the manager of the flat to flat consumer. After the disaster happen : (1) Checking of the condition of the flat dwellers who experience the disasters; (2) Checking of the condition of the buildings are damaged, the type of damage (structural and non-structural), and measures anticipated; (3) Improved method to save themselves; (4) Rehabilitation timely and build back better; (5) Maintenance and check on the condition of the building towers at regular interval. Keywords: Mitigation, Flats, Quality Control